2022
DOI: 10.24867/jged-2022-2-015
|View full text |Cite
|
Sign up to set email alerts
|

Online learning during COVID-19 pandemic as perceived by the students of Graphic engineering and design

Abstract: In this work we wanted to determine how students of Graphic engineering and design perceived online learning a year after the transition from traditional to online classes. The goal was to better understand problems, challenges, and good sides of online learning in this study field, and determine factors that impede knowledge transfer. The students' responses were collected via an anonymous online survey, which consisted of a series of questions that covered: conditions in which online classes are attended, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In relation to F5-Emotional Resources Management, the literature supports that students' mental health has been severely affected, being one of the most cited factors. The reported social impact during the pandemic [32][33][34]36] might have left repercussions that students still need to overcome, such as anxiety, depression, sleep disorder or poor sleep. The findings of these works corroborate this study's results that there was a significant decrease in their emotional resources management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relation to F5-Emotional Resources Management, the literature supports that students' mental health has been severely affected, being one of the most cited factors. The reported social impact during the pandemic [32][33][34]36] might have left repercussions that students still need to overcome, such as anxiety, depression, sleep disorder or poor sleep. The findings of these works corroborate this study's results that there was a significant decrease in their emotional resources management.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly with regard to students in higher education, research reports that the pandemic had an impact on several dimensions of students' lives, including their lifestyle, interpersonal competences, behaviors, emotions, feelings, and educational experiences [19,[30][31][32]. Studies from different parts of the globe indicate some common issues experienced by students, such as a decrease in motivation due to social aspects and especially a lack of communication and interactions with teachers and peers [33][34][35][36]. In a systematic literature review carried out at the beginning of the pandemic crisis in 2020 on The Impact of Social Isolation and Loneliness on the Mental Health of Children and Adolescents in the Context of COVID-19, the authors found 83 articles that addressed this topic [37].…”
Section: Impact Of Covid-19 On Studentsmentioning
confidence: 99%